Tinjauan Etika Deontologi terhadap Penerapan Teknologi In Vitro Fertilization (IVF) - Ira Rahmawati; Labibah Fatihatu Hanin; Tri Cahyanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Vitro Fertilization (IVF) technology is a biotechnological innovation that helps infertile couples conceive. However, the application of this technology has raised ethical debates regarding the nature of life, human dignity, and the moral boundaries of artificial reproduction. This article aims to examine the practice of IVF through an ethical deontology perspective, a moral approach that emphasizes obligations, principles, and respect for human beings as ends, not means. The research method used is a literature review with a descriptive-analytical approach to bioethics and moral philosophy literature. The results of the study indicate that based on deontological ethics, the application of IVF can be considered moral if it respects human dignity, does not treat embryos as mere objects, and is carried out with intentions that are in accordance with human moral obligations.